2008
DOI: 10.1016/j.addbeh.2007.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral couples therapy for comorbid substance use disorders and combat-related posttraumatic stress disorder among male veterans: An initial evaluation

Abstract: Outcomes after behavioral couples therapy (BCT) were compared for 19 dually-diagnosed veterans with combat-related PTSD and a substance use disorder (SUD, primarily alcohol dependence) and 19 veterans with SUD only. Clients with and without comorbid PTSD had very similar pre-treatment clinical profiles on dimensions of substance misuse, relationship functioning, and psychological symptoms. Further, both PTSD and non-PTSD clients showed good compliance with BCT, attending a high number of BCT sessions, taking A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 15 publications
0
28
0
Order By: Relevance
“…Individuals with SUDs whose families are involved in care are more compliant with treatments and experience more positive outcomes than those who do not have the involvement and support of family members (Rotunda, O'Farrell, Murphy, & Babey, 2008). Yet, lack of information, exclusion from treatment, and inability to contact providers are common complaints of family members who want to provide help (England-Kennedy & Horton, 2011).…”
Section: Future Research Directionsmentioning
confidence: 99%
“…Individuals with SUDs whose families are involved in care are more compliant with treatments and experience more positive outcomes than those who do not have the involvement and support of family members (Rotunda, O'Farrell, Murphy, & Babey, 2008). Yet, lack of information, exclusion from treatment, and inability to contact providers are common complaints of family members who want to provide help (England-Kennedy & Horton, 2011).…”
Section: Future Research Directionsmentioning
confidence: 99%
“…Individuals with behavioral health difficulties whose families are involved in care, including but not limited to involvement in family therapy, adhere better to treatment regimens and experience more positive outcomes than those lacking such assistance (Biegel et al ., 2007; Brent & Giuliano 2007; Nelson & Sullivan 2007; Rotunda, et al, 2008). Yet lack of information, exclusion from treatment, and inability to contact providers are common complaints of family members who want to provide help.…”
Section: Introductionmentioning
confidence: 99%
“…As Moreland and colleagues (2012) illustrate, some reduction in aggression following PTSD treatment has been illustrated, but for some Veterans, aggression continues to remain a challenge following reduction of symptoms commonly correlated with aggression. For example, Rotunda and colleagues (2008) found that in a small preliminary study investigating couples therapy for co-occurring PTSD and SUD among veterans, some couples experienced substantial reductions in male to female intimate partner violence following treatment, but the extent to which this intervention was effective was primarily associated with the Veteran’s PTSD diagnosis. Among civilian populations, literature has illustrated vastly differing typologies and patterns of aggressive behavior (Capaldi & Kim, 2007; Holtzworth-Munroe & Stuart, 1994; Johnson, 2008).…”
Section: Discussionmentioning
confidence: 99%